Factors promoting and limiting antimicrobial resistance in the environment – Existing knowledge gaps - Goryluk-Salmonowicz, Agata; Popowska, Magdalena (Frontiers in Microbiology, 2022)
The dissemination of multidrug-resistant bacteria strains and genes carrying antibiotic resistance is currently considered to be one of the most important global problem. The WHO calls for the need to contain the spread of Antimicrobial Resistance (AMR) from all possible sources. There have been many international actions grouping scientists studying this phenomenon, and quite a lot of scientific projects devoted to this problem have already been carried out. As well, so far several strategies have been developed that can inhibit the AMR spread. In this mini-review, we highlight overlooked aspects that seem to be crucial for creating a comprehensive picture of AMR, especially in the context of One Health approach.